A comparative study of graft uptake in split skin grafting between the first postoperative dressing done on day 3 versus day 5 - Yalagachin, Gurushantappa; Hiregoudar, Abhijit D.; Mashal, Sanjay B.; Bagur, Ashika; Shivaramu, Naveena G. (International Surgery Journal, 2021)
Background: Skin grafting offers a method of regaining skin continuity. The common causes of skin graft failure are hematoma, seroma, infection. These affect the graft uptake maximally in the initial postoperative period by impairing graft adherence and subsequent revascularization. Aim of study was to compare graft uptake, rejection, seroma and infection among first postoperative dressing on day 3 versus day 5. Methods: A comparative, prospective study conducted at our institute from November 2015 to April 2021, with 100 patients who underwent SSG (split skin grafting) who were distributed into two groups. Group A underwent the first postoperative dressing on day 3 and group B on day 5. The second postoperative dressing was done 2 days following the first. The grafted site was then assessed on for the percentage of graft uptake, rejection, seroma, infection clinically and through culture and sensitivity. Results: The mean graft uptake in group A was 88.48% whereas in group B was 82.62% in the first dressing and in the second dressing, group A was 88.14% whereas group B was 78.02%, with statistically significant data and thus showing less rejection and infection rate in group A. Seroma was present in 82% of cases in group A and 74% in group B on 1st postoperative dressing which reduced to 6% and 12% respectively with the 2nd dressing. Conclusions: Thus, the first postoperative dressing done on Day 3 following skin grafting, significantly increased the final uptake of the graft, reduced seroma, infection and rejection rate.